Impaired development of a miltefosine-resistant Leishmania infantum strain in the sand fly vectors Phlebotomus perniciosus and Lutzomyia longipalpis - Lieselotte Van Bockstal; Jovana Sádlová; Hamide Aslan Suau; Sarah Hendrickx; Claudio Meneses; Shaden Kamhawi; Petr Volf; Louis Maes; Guy Caljon (International Journal for Parasitology: Drugs and Drug Resistance, 2019)
Objectives: To gain insight into the propagation of miltefosine (MIL) resistance in visceral leishmaniasis, this laboratory study explored development of resistant parasites with a defective miltefosine transporter (MT) in sand flies. Methods: Infectivity, colonization of stomodeal valve and metacyclogenesis of a MIL-resistant (MIL-R) Leishmania infantum LEM3323 line with a defective MT were assessed in the natural sand fly vectors Phlebotomus perniciosus and Lutzomyia longipalpis. Given our recent description of partial drug dependency of the MT-deficient line, the impact of MIL pre-exposure on sand fly infectivity was explored as well. Results: A significant reduction in sand fly infection, stomodeal valve colonization and differentiation into metacyclics (determined by a lower flagellum/cell body length ratio) was observed in both vectors for MIL-R as compared to the isogenic parent MIL-susceptible line. Re-introduction of the wildtype MT gene into MIL-R tended to partially rescue the capacity to infect sand flies. Pre-exposure to MIL did not alter infectivity of the MIL-R line. Conclusion: The MIL resistant L. infantum LEM3323 line is significantly hampered in its development and transmissibility potential in two sand fly vector species. Additional studies are warranted to evaluate whether this applies to other visceral Leishmania parasites with acquired MIL-resistance. Keywords: Leishmania infantum, Miltefosine-resistance, Phlebotomus perniciosus, Lutzomyia longipalpis, Metacyclogenesis, Fitness